The Influence of Arbitrary Breakpoints on Judgments of Maximum Output - Palmeira, Mauricio; Andrade, Eduardo; Sharifi, Shahin; Mao, Wen; Jacob, Jorge (Journal of Consumer Psychology, 2020)
Consumers often wonder about the product's maximum output: the highest rotation speed of a blender or the best printing quality of a printer. We examine how the number of levels (e.g., a blender with 3 vs. 7 speeds) influences judgments of maximum product output. Objectively speaking, the number of levels is no more than a set of breakpoints in an already predetermined continuum from the product's minimum to maximum output. Nevertheless, because of the ubiquitous association between number of breakpoints and quantity in daily life, consumers do not simply view more levels as a signal of greater precision (i.e., giving consumers more control over the possible outputs). They also incorrectly believe that the product has greater power (i.e., a higher maximum output), even when such an inference is in conflict with diagnostic attribute information (e.g., watts). A series of five studies documents the phenomenon, its asymmetric nature, and its boundary conditions. Reliance on the inaccurate “more levels, more power” lay theory weakens when participants consider a reduction rather than an increase in number of levels, and it disappears when the consumer is presented with an explicit relationship between each level and its corresponding output value (e.g., level 4:400 W).